Collaborative digital marketing and supply chain management for micro, small and medium enterprises - Agus Mansur; Razel Thimoty; Syafa Thania Prawibowo; Wahyudi Sutrino; Fadhil Adita Ramadhan; Tiara Febian (International Journal of Industrial Optimization, 2025)
This study explores specific supply chain challenges faced by Batik Ayu Arimbi, a small-scale business in the batik industry, particularly how the manual calculations in its make-to-stock system impact its financial accuracy and operational efficiency. The company has been experiencing financial losses due to these inaccuracies. To address these issues, this research proposes improvements in supply chain management by implementing Business Process Model Notation (BPMN) to streamline process visualization and coordination among the artisans, showrooms, and production houses. The use of digital marketing platforms, particularly Instagram, is also suggested to optimize marketing efforts and achieve sales targets. This study contributes to the literature by emphasizing novel BPMN implementation aspects and demonstrating the effectiveness of digital marketing for MSMEs in the textile sector. The qualitative data was collected through semi-structured interviews, which provided insights into current practices and areas for improvement. The findings show that increased cooperation between supply chain actors reduces inventory errors by 20% and increases the accuracy of financial tracking by 15%, thereby reducing operational risks. Furthermore, the digital marketing strategies increased customer engagement rates by 25%, directly contributing to sales growth. The findings further suggest that the proposed solutions not only resolve the identified problems but also provide a scalable model for enhancing resilience in Batik Ayu Arimbi’s supply chain operations as one of MSMEs. In conclusion, boosting sustainability and performance in MSMEs requires improved supply chain collaboration and the strategic application of digital tools.